Effect of Smoking on the Development of Migraine in Women: Nationwide Cohort Study in South Korea - Seung Ae Kim; Kyungdo Han; Soyoun Choi; Michelle Sojung Youn; Hyemin Jang; Mi Ji Lee (JMIR Publications, 2024)
Abstract BackgroundSmoking is known to be a significant risk factor for various diseases. Migraine, a condition requiring careful lifestyle management, currently lacks specific guidelines advocating for smoking cessation as a preventive measure. Although cross-sectional studies have suggested a potential link between smoking and an increased risk of migraine, the findings have been inconsistent and conflicting. To date, there has been no longitudinal study which investigated the effect of smoking on the risk of migraine in a prospective setting. ObjectiveThis longitudinal study aimed to investigate the impact of smoking on the incidence of migraine in women and examine the modifying effect of menopausal status. MethodsUsing nationally representative National Health Insurance Service (NHIS) data, women aged ≥40 years who participated in national breast cancer screening in 2009 were followed-up until the end of 2019. Baseline data on smoking status (non-, ex-, and current smoker) as well as the duration and amount of cigarette smoking were collected. A Cox proportional hazards regression model was used to examine the independent effect of smoking on the risk of incident migraine after adjusting for demographics, comorbidities, and female reproductive factors. The results were stratified by menopausal status, and an interaction analysis (smoking × menopause) was performed. ResultsIn total, 1,827,129 women were included in the analysis. Women with a history of smoking exhibited a higher risk of developing migraine, compared with nonsmokers. Specifically, a higher risk of migraine was observed in women with past (adjusted hazard ratio [HR] 1.044, 95% CI 1.000-1.089) and current cigarette use (adjusted HR 1.050, 95% CI, 1.023-1.079) than in nonsmokers. The effect was greater in premenopausal women (adjusted HR 1.140, 95% CI, 1.108-1.172) than in postmenopausal women (adjusted HR 1.045, 95% CI 1.018-1.073; PP ConclusionsSmoking increases the risk of migraine in women, with a dose-dependent relationship. Menopause modifies this effect. Our findings suggest that smoking is an important modifiable risk factor of migraine, with a higher impact in premenopausal women. The interaction between smoking and estrogen may increase the vulnerability of the migraine brain.